PENERAPAN MODEL PEMBELAJARAN INKUIRI DENGAN SCIENTIFIC APPROACH DALAM UPAYA MENINGKATKAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS XII IPS 2 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2018/2019 - Wahyuniyati, Ayu (LPPM IKIP PGRI Bali, 2020)
The purpose of this study was to find out the understanding of the material and students' responses systematically, in detail on the application of inquiry learning models with a scientific approach to the material of short and simple songs in class XII. This research is a classroom action research designed through action in classroom learning activities. The subject of this research is students of class XII IPS 2 of SMA Negeri 7 Denpasar in the 2018/2019 academic year in the even semester, and the object of research is understanding students' material and responses. The results of the action research showed that the application of the inquiry learning model was found to be successful in improving students' understanding of short and simple song material. This can be seen from the average value of pre-cycle comparison, cycle I, and cycle II there is an increase. This research has met the determined indicators of success, so that the application of inquiry learning models can improve students' understanding of short and simple song material. There was a student response to the application of the inquiry learning model to improve the ability to understand short and simple song material in class XII IPS 2 students of SMA Negeri 7 Denpasar in the 2018/2019 academic year.